Solitary collagenoma of the labium majus: A rare occurrence - Kavita Bisherwal; Archana Singal; Deepika Pandhi; Vaibhav Girotra (Wolters Kluwer Medknow Publications, 2017)
Collagenomas are connective tissue nevi representing hamartomatous proliferation of collagen. Isolated collagenomas are of rare occurrence. They are sporadically acquired, and lesions are often localized to a single body region. We described a case of solitary collagenoma in a 23-year-old woman, confirmed on histopathology and special stains for collagen, involving an uncommon site such as labium majus. A high index of suspicion for a skin-colored circumscribed solitary growth and a low threshold for biopsy often help to arrive at a final diagnosis.